Long‐term real‐world outcomes of patients with acute promyelocytic leukaemia treated with arsenic trioxide and all‐trans retinoic acid without chemotherapy—a retrospective, single‐centre study. (18th December 2022) - Singh, Charanpreet; Yanamandra, Uday; Karunakaran, Parathan; Jindal, Nishant; Kumar, Saloni Rani; Saini, Neha; Jandial, Aditya; Jain, Arihant; Das, Chandan; Lad, Deepesh; Prakash, Gaurav; Khadwal, Alka; et al.
Summary: Arsenic trioxide (ATO) and all‐trans retinoic acid (ATRA) form the backbone of the treatment of acute promyelocytic leukaemia (APL), with the addition of chemotherapy for high‐risk patients. We describe our experience of treating patients with APL of all risk classes with ATO and ATRA without chemotherapeutic agents. Patients received induction with ATO and ATRA followed by three cycles of consolidation with ATO and ATRA (each 1 month apart) after achieving morphological remission. Patients with intermediate‐ and high‐risk disease received a further 2 years of maintenance with ATRA, 6‐mercaptopurine and methotrexate. A total of 206 patients were included in the study. The majority of the patients were intermediate risk (51.9%), followed by high risk (43.2%). Differentiation syndrome was seen in 41 patients (19.9%). Overall, 25 patients (12.1%) died within 7 days of initiating therapy. Seven patients relapsed during follow‐up. The mean (SD) estimated 5‐year event‐free survival (EFS) and overall survival (OS) in the entire cohort was 79% [5.8%] and 80% [5.8%] respectively. After excluding patients who died within 7 days of therapy initiation, the mean (SD) estimated 5‐year EFS and OS was 90% [5.8%] and 93% [3.9%] respectively. Our study shows that treatment of all risk classes of APL with ATO and ATRA without chemotherapy is associated with excellent long‐term outcomes in the real‐world setting.